IMPLEMENTASI UANG BEREDAR (M2) SEBAGAI PUBLIC GOODS AND FLOW CONCEPT DAN UANG SEBAGAI PRIVATE GOODS AND STOCK CONCEPT - SRI RAMADHAN (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". This paper tries to discuss the issue of money supply (M2) as public goods and stock concept and public goods and flow concept. The point of the problem discussed is about the function of money economically Islam and convention then how the implementation of money supply (M2) as public goods and flow concept and money supply (M2) as private goods and stock concept. To find the answer to this problem, use a literature study using the hermeneutical approach by looking at the money supply data in a broad sense (M2) per year 2014 to 2016 published by Bank Indonesia. It is concluded that the function of money from an Islamic economic point of view is as a means of exchange and a unit of value, while in conventional economics the function of money apart from the two points plus money as a means of exchange of wealth, money as a standard of delay payment. Furthermore from the money supply data (M2) illustrated that money circulating in the position of money that is public goods and stock concept. This Stock concept illustrates the weakness of M2 growth that is affected by the contraction of Government's financial operations. This is reflected in the increase of government deposits, BI and Banking. Deposits are more channeled on business activities in the form of stock concept, such as property loans, compared to Working Capital Loans. While in view of Islamic economy money is public goods and flow concept not public goods and stock concept. Because in Islamic economics there can be no accumulation of money at one point, meaning money must flow like a flowing water. If the position of money in the stock concept, it will damage the flow of the economy of society.